Analisis Tingkat Kepuasan Pengguna Sistem Informasi Akademik Menggunakan Metode EUCS - Wan Rezalina (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The Student Academic Information System (SIAM) is a system specifically designed to process academic information on students from the Riau Ministry of Health Poltekkes since 2015. This system is a web-based information system designed to meet minimum requirements. for processing student academic information, starting with data processing. Problems that arise when applying SIAM are that SIAM experiences errors such as not being able to access several menus at home, online libraries, e-learning, and email cannot be accessed or errors, the forgot password feature cannot be accessed, and information services are not available on the SIAM help menu. This study aims to measure the level of user satisfaction using the End User Computing Satisfaction (EUCS) method. The method is based on 5 variables namely Content, Accuracy, Format, Easy Of Use, and Timeliness. Questionnaire data processing using SmartPLS Software. The results showed that the satisfaction level of SIAM users was in the moderate range with a value of 0.634. Because users are satisfied with the information content generated according to their needs, easy to understand, complete, displays correct and accurate information, and the system never has an error, the required information can be obtained quickly through SIAM, and always displays the latest information